Fluctuations of CO₂ and 222Rn concentration in the karst vadose zone: Comparing exhalation, indoor concentrations, and cave air dynamics (Nerja Cave, Southern Spain) - Liñán-Baena, Cristina; Vadillo-Pérez, Iñaki; Benavente, J.; Cañete-Hidalgo, Sergio Andrés; Ojeda-Rodríguez, Lucía (Elsevier, 2025)
To investigate the influence of atmospheric and subsurface karst conditions on gas transport in the vadose zone and across the epikarst-atmosphere interface, we measured: a) radon (222Rn) and carbon dioxide (CO2) concentrations in the air of two boreholes drilled in the vadose zone, where high levels of these gases had been previously reported, and b) indoor radon concentrations in two dwellings built on potentially karstifiable lithologies. One dwelling (D1) is located near the boreholes and a major tourist cave (Nerja Cave), while the other (D2) is in the town of Nerja. Periodic fluctuations in gas concentrations were observed in the boreholes, reflecting advective transport of atmospheric air into the subsurface (inflow) and from the vadose zone into the atmosphere (outflow). Gas transport was mainly driven by barometric pumping, whose efficiency depends on vadose zone permeability, although thermal-induced convection was also detected. Advective transport was more effective in winter than in summer. In the dwellings, high 222Rn concentrations resulted from subsurface radon infiltration into the buildings. Radon transport indoors was mainly driven by depressurization of the dwellings due to temperature gradients and barometric pumping (D1), as well as wind effects and ventilation habits (D2). The presence of large karstic cavities may play a supplemental role in the indoor radon concentrations in nearby buildings. Finally, some anomalies in vadose air radon concentrations appear to be linked to seismic activity, though further research is needed to confirm this relationship.
Keywords: Cuevas - Ventilación; Karst; Gases - Análisis; Karst vadose ventilation; Boreholes; Radon; CO2; Ground air; Meteorological parameters